Knowledge discovery, knowledge engineering and knowledge management : 9th International Joint Conference, IC3K 2017, Funchal, Madeira, Portugal, November 1-3, 2017, Revised selected papers /: 9th International Joint Conference, IC3K 2017, Funchal, Madeira, Portugal, November 1-3, 2017, Revised selected papers. ([2019]) - Unknown
No abstract available